2006
DOI: 10.1111/j.1600-6143.2006.01510.x
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Iron Released During Machine Perfusion Predicts Viability of Ischemically Injured Deceased Donor Kidneys

Abstract: Redox-active iron, catalyzing the generation of reactive oxygen species, has been implicated in experimental renal ischemia-reperfusion injury. However, in clinical transplantation, it is unknown whether redoxactive iron is involved in the pathophysiology of ischemic injury of non-heart-beating (NHB) donor kidneys. We measured redox-active iron concentrations in perfusate samples of 231 deceased donor kidneys that were preserved by machine pulsatile perfusion at our institution between May 1998 and November 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Further research is warranted to investigate associations between donor hemodynamic profiles and processes contributing to organ injury. Investigation of associations between renal perfusate biomarkers and donor hemodynamics is a logical direction for future research (26)(27)(28)(29). Although our findings indicate that certain parameters may be associated with inferior outcomes, it is unlikely that any one hemodynamic measure will be sufficient to describe relevant physiological changes (eg, donors with the same AUCSBP could have radically different SBP trajectories).…”
Section: Discussionmentioning
confidence: 86%
“…Further research is warranted to investigate associations between donor hemodynamic profiles and processes contributing to organ injury. Investigation of associations between renal perfusate biomarkers and donor hemodynamics is a logical direction for future research (26)(27)(28)(29). Although our findings indicate that certain parameters may be associated with inferior outcomes, it is unlikely that any one hemodynamic measure will be sufficient to describe relevant physiological changes (eg, donors with the same AUCSBP could have radically different SBP trajectories).…”
Section: Discussionmentioning
confidence: 86%
“…40 This parameter independently predicts viability of ischemically injured kidneys, particularly those from NHB donors. 41 Especially when used in combination, viability markers are an important means of deciding which donated organs to use for transplantation. (The value of a pretransplantation renal biopsy as a tool to assess viability is controversial; in kidneys from elderly NHB donors, severe arteriosclerosis seems to have an adverse effect on graft survival and GFR.…”
Section: Discussionmentioning
confidence: 99%
“…28 We have previously reported that higher concentrations of redox-active iron in the renal preservation solution are associated with increased risk of primary non-function in clinical kidney transplantation. 5 Since lower levels of haptoglobin will lead to higher levels of free haemoglobin -containing redox-active iron in its haeme group -our current findings have biological plausibility and fit into an established theoretical framework. Although we were able to identify almost 50% of the spots picked from the Sypro Ruby-stained gel, the identity of the other differentially expressed protein spots unfortunately could not be identified by MALDI-TOF/TOF, or by additional attempts using electrospray ionization tandem mass spectrometry.…”
Section: Discussionmentioning
confidence: 79%